Does Reporting Transparency Affect Industry Coordination? Evidence from the Duration of International Cartels - Goncharov, Igor; Peter, Caspar David (The Accounting Review, 2019)
ABSTRACT Firms coordinate their actions with industry peers, thereby affecting product market competition. Using the cartel setting, we investigate how financial reporting transparency affects industry coordination. Economic theory predicts that transparency might either prolong cartel duration through increased contracting efficiency, or destabilize cartels due to earlier detection of deviating members. We test these predictions on firms indicted by the European Commission for anticompetitive behavior between 1980 and 2010. Using reporting under internationally recognized accounting standards (IFRS or U.S. GAAP) as our measure of reporting transparency, we find that following a transparent accounting framework decreases cartel duration. We show this finding is partly explained by transparent segment disclosure, which provides a means for the verification of agreed-upon sales for a product or region. Consistent with the view that transparent reporting leads to earlier detection of deviating members, we further show that transparency lowers cartel duration when the likelihood of cheating is high.